Metabolic Energy Contributions During High-Intensity Hatha Yoga and Physiological Comparisons Between Active and Passive (Savasana) Recovery - Lee, Kwang-Ho; Ju, Hyo-Myeong; Yang, Woo-Hwi (Frontiers in Physiology, 2021)
Purpose: The objective of this study was to investigate metabolic energy contributions during high-intensity hatha yoga (HIHY) and to compare changes in physiological variables between active and passive recovery methods. Methods: The study involved 20 women yoga instructors (n = 20) who performed 10 min of HIHY (vigorous sun salutation). Upon completion, they were randomly assigned to either active (walking; n = 10) or passive (savasana; n = 10) recovery groups for a period of 10 min. During HIHY, physiological variables such as heart rate (HRpeak and HRmean), oxygen uptake (VO2peak and VO2mean), and blood lactate concentrations (peak La−) were measured. Energetic contributions (phosphagen; WPCR, glycolytic; WGly, and oxidative; WOxi) in kJ and % were estimated using VO2 and La− data. Furthermore, the metabolic equivalents (METs) of VO2peak and VO2mean were calculated. To compare different recovery modes, HRpost, ΔHR, VO2post, ΔVO2, recovery La−, and recovery ΔLa− were analyzed. Results: The results revealed that HRpeak, VO2peak, and peak La− during HIHY showed no differences between the two groups (p > 0.05). Values of HRpeak, HRmean, METs of VO2peak and VO2mean, and La− during HIHY were 95.6% of HRmax, 88.7% of HRmax, 10.54 ± 1.18, 8.67 ±.98 METs, and 8.31 ± 2.18 mmol·L−1, respectively. Furthermore, WOxi was significantly higher compared with WPCR, WGly, and anaerobic contribution (WPCR + WGly), in kJ and % (p < 0.0001). VO2post and recovery ΔLa− were significantly higher in the active recovery group (p < 0.0001, p = 0.0369, respectively). Values of ΔVO2 and recovery La− were significantly lower in the active group compared with the passive group (p = 0.0115, p = 0.0291, respectively). Conclusions: The study concluded that high-intensity hatha yoga which was performed for 10 min is a suitable option for relatively healthy people in the modern workplace who may have hatha yoga experience but do not have time to perform a prolonged exercise. Following active recovery, they can participate in further HIHY sessions during short breaks. Furthermore, a faster return to work can be supported by physiological recovery.